Introducing eJP - Robert M Frederickson; Malcolm K Brenner (Molecular Therapy, 2010)
Background Altered immunoglobulin G (IgG) glycosylation was implicated in various conditions, but its role in fibromyalgia (FM) remains unclear. This study investigated IgG glycosylation patterns in FM patients and associations between glycosylation changes and clinical profiles. Methods We recruited 30 FM patients and 30 healthy controls. Sleep quality (Pittsburgh Sleep Quality Index, PSQI), anxiety (Beck Anxiety Inventory, BAI), depression (Beck Depression Inventory, BDI), widespread pain (Widespread Pain Index), symptom severity (Symptom Severity Scale), functional impact (FM impact questionnaire, FIQ), pain intensity (Visual Analog Scale), and pressure pain threshold were evaluated at baseline in both groups and after 6 months in FM patients. Glycosylation traits were quantified for IgG1, IgG2, and combined IgG3/4. Partial Least Squares explored multivariate associations between glycosylation and clinical changes. Hierarchical clustering explored glycosylation-change subgroups and compared clinical changes across them. Results FM patients had higher baseline PSQI, BAI, and BDI scores than controls, whereas the baseline IgG glycosylation differences were nominal. Nominal longitudinal differences were observed in PSQI, IgG1-bisecting, IgG1-sialylation, IgG3/4-monogalactosylation, and IgG3/4-agalactosylation. The full 20-marker longitudinal PLS model was not significant, but in an exploratory reduced model selected from the same data, three IgG3/4 galactosylation-axis markers were associated with affective and functional change scores. This latent dimension correlated with changes in BAI (r = -0.76), BDI (r = -0.77), and FIQ (r = -0.76). Exploratory clustering suggested three glycosylation-change subgroups. Conclusion IgG3/4 glycosylation changes may track affective and functional symptom changes in FM, but these exploratory findings require validation in larger independent cohorts. Significance statement This study suggested that IgG glycosylation profiles were associated with clinical trajectories in fibromyalgia and could be used to classify the patients into specific subgroups. The findings supported the potential role of immune dysregulation in FM pathophysiology and the value of glycosylation profiling for personalized medicine, in which IgG glycosylation could be considered as biomarkers supporting diagnosis, prognosis, and decision-making in fibromyalgia management.